2014
DOI: 10.1111/cns.12342
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Tolerogenic Dendritic Cells Pulsed with MOG Autoantigen in Experimental Autoimmune Encephalomyelitis

Abstract: We found that VitD3-TolDC-MOG treatment showed a beneficial effect, not only decreasing the incidence of the disease but also reducing the severity of the clinical signs mediated by induction of regulatory T cells (Treg), as well as IL-10 production and reduction of Ag-specific lymphoproliferation. Our results support VitD3-TolDC-peptide(s) treatment as a potential strategy to restore tolerance in autoimmune diseases such as MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 26 publications
7
81
1
Order By: Relevance
“…Given that tolDC are relatively stable in phenotype and function (13), autologous tolDC may be valuable for inducing T cell tolerance (29). Although it might be difficult for tolDC to pass the CNS (26), they did inhibit splenic Th1 and Th17 responses in EAE mice, similar to a previous report (26). In addition, although BD750 did not affect IL-10 production by LPS-stimulated DCs, BD750-DC secreted a low level of but not AKT phosphorylation, consistent with our previous findings (15).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Given that tolDC are relatively stable in phenotype and function (13), autologous tolDC may be valuable for inducing T cell tolerance (29). Although it might be difficult for tolDC to pass the CNS (26), they did inhibit splenic Th1 and Th17 responses in EAE mice, similar to a previous report (26). In addition, although BD750 did not affect IL-10 production by LPS-stimulated DCs, BD750-DC secreted a low level of but not AKT phosphorylation, consistent with our previous findings (15).…”
Section: Resultssupporting
confidence: 80%
“…Previous studies have shown that tolDC can inhibit autoimmune diseases, such as rheumatoid arthritis and EAE, in rodents (24,25). Indeed, pharmacological modification is a new strategy to induce tolDC (10,26). It is well known that the JAK/STAT pathway is crucial for the maturation and tolerance of DCs (16).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this approach demonstrated tolerable safety profiles. Similarly, MS-specific DC-based immunotherapy has been investigated through delivery of exogenously-loaded DCs with MOG 40-55 tolerized with vitamin D 3 , and was shown to ameliorate EAE [71]. Unfortunately, adoptive DC therapy is limited by high cost, inadequate cell sources, and safety concerns [66, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in in vivo studies, it was demonstrated that transplantation of hPMSCs could reduce the symptoms of many autoimmune diseases, for instance, experimental autoimmune encephalomyelitis (EAE), a common animal model of MS [11]. Moreover, Mansilla et al [12] found that induction of CD4 þ CD25 þ FOXP3 þ Treg could reduce the severity of autoimmune diseases such as EAE. The CD4 þ interleukin (IL)-10 þ T-cell subset, a new Treg subset that is involved in the negative regulation in T-cell response, was found in a murine study [13].…”
Section: Introductionmentioning
confidence: 99%